Kajian Baptisan Air Dalam Sejarah Alkitab Dan Implikasinya Bagi Gereja Masa Kini - Situmorang, Benny Andreson; Sembiring, Dina Br (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2025)
For Christians, water baptism is one of the most important doctrines and is a commandment written in the great commission. Therefore, it is very important to be known, understood, comprehended and respected by every believer. However, in reality, Christians often have different opinions and understandings about this. Some are of the view that the baptism of the Spirit and water baptism are the same, some sharpen the differences in terms of the method of baptism. In fact, water baptism has a very important meaning in the lives of Christians. So Christians should think maturely and support each other in carrying out God's commands without having to blame each other. Water baptism is not a church regulation engineered by humans. Baptism is a provision made and conveyed by the Lord Jesus. Even though in the end, people tend to view or consider baptism as a statement of belief from humans alone. Even today many Christians have lost awareness of the meaning and significance of baptism and they consider it an ordinary event. Water baptism is different from the baptism of the Holy Spirit, but the two cannot be separated. Water baptism is a very important dogma but is only a symbol or symbol of purification. Baptism outside of Christianity is different from Christian Baptism.